KONSENTRASI DAN WAKTU PENDEDAHAN EFEKTIF EKSTRAK DAUN SIRSAK (Annona muricata L) SEBAGAI LARVASIDA HAYATI JENTIK Aedes aegypti - Luluk Kusnatin; M. Arief Soendjoto; Eko Rini Indrayatie; Taufiqur Rohman (Universitas Lambung Mangkurat, 2012)
Crop Sirsak (Annona Muricata L.) having potency as larvasida involve. use Larvasida involve the peaceful relative because the residu easy to degradasi and non relative contaminate the environment. This research aim to specify the concentration of extract Annona muricata L leaf effective kill to wiggler of Aedes aegypti, specifying concentration influence with the disclosure time and specify of concentration and disclosure time of extract Annona muricata L leaf with the death wiggler of Aedes aegypti. Kind of Research experimental, by using Complete Random Device two factor , that is concentration of extract Annona muricata L leaf and disclosure time. Result of analysis probit show the concentration of extract Annona muricata L leaf effective kill to wiggler of Aedes aegypti at LC90 with the concentration 459,82 ppm with the disclosure time 24 clock. From research result show the excelsior of concentration of extract Annona muricata L leaf hence longer disclosure time faster. Correlation test show there is correlation betwen concentration of extract Annona muricata L leaf with the death wiggler of Aedes aegypti, level correlation is medium ( r=0,432). While time of disclosure and death wiggler of Aedes aegypti show the strong relation ( r=0,743). Test the regresi show the existence of positive influence concentration of extract Annona muricata L leaf and disclosure time to death wiggler.